Biomedical engineering systems and technologies : 7th International Joint Conference, BIOSTEC 2014, Angers, France, March 3-6, 2014, Revised selected papers /: 7th International Joint Conference, BIOSTEC 2014, Angers, France, March 3-6, 2014, Revised selected papers. (2015) - Unknown
No abstract available